STUDENTS’ PERCEPTIONS OF ENGLISH LEARNING MATERIALS FOR CHILDHOOD EDUCATION THROUGH PJBL MODEL - Fera Zasrianita; Syukri Hamzah; Andriadi Andriadi; Nadrah Nadrah (Linguists : Journal of Linguistics and Language Teaching, 2025)
This study aims to understand the students' perceptions towards the implementation of English language material for early childhood based on project-based learning. This research was a qualitative descriptive study. The method used in this research is the survey method. The subject of this study was a student of the 6th semester at English Language Education who took TEYL courses at FTT UIN FAS Bengkulu. There were 26 (twenty-six) students in the sample for the research. In collecting the data, the researcher used a questionnaire about students' perceptions towards the implementation of project-based learning in designing English learning material for early childhood education. The result of the research clearly showed that project-based learning has a significant impact on student performance in designing English learning material for early childhood education. In designing English learning material for early childhood education. The subject of this study was a student of the 6th semester at English Language Education who took TEYL. There were 26 students in the sample for the research. In collecting the data, the researcher used a questionnaire about students' perceptions towards the implementation of project-based learning in designing English learning material for early childhood education. The result of the research clearly showed that project-based learning has a significant impact on student performance in designing English learning material for early childhood education.